Biological and Chemical Diversity of Coral-Derived Microorganisms - Hou, Xue-Mei; Xu, Ru-Fang; Gu, Yu-Cheng; Wang, Chang-Yun; Shao, Chang-Lun (Current Medicinal Chemistry, 2015)
Coral-derived microorganisms have been a major focus of many research efforts on marine ecology in recent decades. Importantly, research on bioactive compounds from these diverse microorganisms, which include fungi and bacteria, has experienced an explosive growth during the past five years. This has unveiled the ecological roles of these microorganisms, which prevent antifouling, inhibit pathogenic bacteria, and deter predators in ocean ecosystems. Moreover, the structural diversity and pharmacological activity of the compounds produced by these microorganisms have also been studied extensively, leading not only to an understanding their roles within ecosystems, but also the potential value of their use in human health. In this review, 258 marine natural products, including polyketides, terpenoids, meroterpenoids, alkaloids, peptides, shikimates and lipids, all discovered in the past 24 years, are presented. 146 references are cited.
Keywords: Alkaloids